Cultural Dimensions in Sabir Rashid's Novel "Musa’s Sword” - Mohammed Ahmed Hasan; Rasool Hamad Rasool (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
If, the novel served human beings and its cases a lot, especially as a platform In the past, especially in the nineteenth century in Europe, to create the concept of a nation and to build a national state, the novel is moving in another important direction now. It moves towards the globalization of thought and culture, in a way that develops a new perspective within itself, in a way that all cultures and identities can express their existence and their own ways. From this perspective, in order to demonstrate the continued efforts of some Kurdish novelists, based on Kurdish novels, to show the views and views of Kurdish people, they are parallel to the views and views of others, in the different cultures of other nations of the world. We try to view all the different perspectives and the perspectives of the novelist in a way that views the different cultures, the values and measurements of the material and spiritual differences of human beings. Let's show in detail the views of agreements and disagreements of the perspectives of the characters, and their events which show the intellectual development and knowledge of the characters and events, the self-and-subjective reasons behind the continued rise of events, especially since these analyses have not been conducted in the past. On the other hand, one of the most important and vibrant aspects of all human societies is culture as a basis for human life and harmony with its surroundings. At the same time, as a general framework for knowing and being familiar with the structure and nature of individuals and communities, at the same time to recognize all the human phenomena and events that are happening in the communities. From this point of view, through Kurdish novels, we want to have a look at the cultural differences in the context and geography of Kurdistan between different cultures and neighbors, and have recorded a history of coexistence and ideological and religious conflict. One of the new works in this field is the novelist (Sabir Rashid), as a large scope of the novel, but the main events is based on cultural differences and numerousness, while the novel has not been thoroughly researched, so it will have its own importance and importance in this field.